Case Report: Allergic Bronchopulmonary Aspergillosis Revealing Asthma - Snen, Houda; Kallel, Aicha; Blibech, Hana; Jemel, Sana; Salah, Nozha Ben; Marouen, Sonia; Mehiri, Nadia; Belhaj, Slah; Louzir, Bechir; Kallel, Kalthoum (Frontiers in Immunology, 2021)
Allergic bronchopulmonary aspergillosis (ABPA) is an immunological pulmonary disorder caused by hypersensitivity to Aspergillus which colonizes the airways of patients with asthma and cystic fibrosis. Its diagnosis could be difficult in some cases due to atypical presentations especially when there is no medical history of asthma. Treatment of ABPA is frequently associated to side effects but cumulated drug toxicity due to different molecules is rarely reported. An accurate choice among the different available molecules and effective on ABPA is crucial. We report a case of ABPA in a woman without a known history of asthma. She presented an acute bronchitis with wheezing dyspnea leading to an acute respiratory failure. She was hospitalized in the intensive care unit. The bronchoscopy revealed a complete obstruction of the left primary bronchus by a sticky greenish material. The culture of this material isolated Aspergillus fumigatus and that of bronchial aspiration fluid isolated Pseudomonas aeruginosa. The diagnosis of ABPA was based on elevated eosinophil count, the presence of specific IgE and IgG against Aspergillus fumigatus and left segmental collapse on chest computed tomography. The patient received an inhaled treatment for her asthma and a high dose of oral corticosteroids for ABPA. Her symptoms improved but during the decrease of corticosteroids, the patient presented a relapse. She received itraconazole in addition to corticosteroids. Four months later, she presented a drug-induced hepatitis due to itraconazole which was immediately stopped. During the monitoring of her asthma which was partially controlled, the patient presented an aseptic osteonecrosis of both femoral heads that required surgery. Nine months after itraconazole discontinuation, she presented a second relapse of her ABPA. She received voriconazole for nine months associated with a low dose of systemic corticosteroid therapy with an improvement of her symptoms. After discontinuation of antifungal treatment, there was no relapse for one year follow-up.